Penerapan Model Time Token Berbantuan Media Kartu Kuartet Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Amalia Faiz Amalia; Mila Roysa; Erik Aditia Ismaya (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2020)
This study aims to analyze the improvement of student learning outcomes in class IV SD N Tlogoharum 01 in the academic year 2019/2020. The research method used is classroom action research. The subjects of this study were students in grade IV SD N Tlogoharum 01, totaling 14 students. The research phase consists of planning, action, observation, reflection. Data collection methods for interviews, observations, tests and documentation. Data collection instruments used in the form of observation, tests and documentation. The data analysis technique used is descriptive qualitative and quantitative data analysis techniques. Before conducting class action research, namely student learning outcomes for Indonesian Language and social studies subjects IV grade is low. The pre-cycle conditions indicate that in Indonesian content there are 6 students who achieve mastery with an average grade of 70 while in social studies only 5 students who achieve mastery with an average grade of 67. The results showed that the learning outcomes of Indonesian students charge the cognitive domain in cycle I was 69 with 58% classical completeness and in cycle II the class average increased to 77 and classical completeness reached 78%. Furthermore, the average class IPS load in cycle I 73 with a classical completeness of 65%, then increased in the second cycle experienced a significant increase to 82 and classical completeness achieved, which is 85%. While the indicators of success, which is 75%.